Antianaemic property of Ficus capensis leaves and its combination with Cnidoscolus aconitifolius leaves in phenylhydrazine-induced anemic rats - Obiajulu Christian Ezeigwe; Chidinma Felicia Ezennaya; Ebele Lauretta Iloanya; Chioma Henrietta Obi; Nma Helen Ifedilichukwu; Chisom Miracle Okeke (Shahrekord University of Medical Sciences, 2022)
Introduction: Anemia is a common health condition caused by a decrease in red blood cells. Some medicinal plants are used as a remedy to treat anemia. This study compares the anti-anemic properties of different doses of the aqueous extracts of Ficus capensis (AEFC) and its combination with the aqueous extract of Cnidoscolus aconitifolius (AECA) in phenylhydrazine-induced anemic rats. Methods: Anemia was induced by intraperitoneal injection of 20 mg/kg phenylhydrazine for five consecutive days. Graded doses of the extracts were given by oral gavage once a day continuously for 30 days. At the end of the treatment, blood was collected for hematological analysis. Results: The antianemic effects of AEFC and its combination with AECA were demonstrated by significant increases (P < 0.05) in the hemoglobin (HGB), packed cell volume (PCV) and red blood cell (RBC) count of the extract-treated groups compared to the anemic control group. There was a better increase in the HGB levels of a combination of 400 mg/kg AEFC + AECA (13.97 ± 2.53) compared to 400 mg/kg AEFC (12.06 ± 0.02). The PCV increased more in 400 mg/kg combination of AEFC + AECA (41.94 ± 0.37) compared to 400 mg/kg AEFC (36.31 ± 1.51). A significant (P < 0.05) increase was observed in the RBC count of a combination of 400 mg/kg AEFC + AECA (6.36±0.51) compared to 400 mg/kg AEFC (4.75 ± 0.46). Conclusion: Although AEFC improved the haematological parameters of the animals when administered alone, its combination with AECA yielded a far much better result by totally restoring the haematological parameters of the phenylhydrazine-induced anemic rats to normal.